High‐resolution remote sensing for quantifying vegetation structure as avian habitat - Seth Harju; Tarita Harju; Jodi Berg; Richard Alward; Scott Cambrin (Wildlife Society Bulletin)
Abstract Monitoring trends in the structure and composition of vegetation structure is a critical part of land and wildlife management. Advanced tools and technologies can help reduce the cost and improve the implementation of such monitoring. Most applications of remote‐sensing technologies, however, focus on either vegetation structure reflecting habitat requirements of a single avian species or on general measures of ecosystem productivity or biodiversity. While important, these applications ignore the needs of many applied land and wildlife managers who are often legally or administratively tasked with managing landscapes for multiple avian species with divergent habitat requirements. We used current state‐of‐the‐art technologies to assess vegetation structure in a dryland riparian ecosystem and compared this structure to avian nesting habitat metrics. We demonstrated how 3‐dimensional canopy structure, including multi‐layer canopy cover, voxelized leaf area density, and habitat‐based patch‐level leaf area density, can be quantified and tied to each species' a priori known nesting habitat. We evaluated these results in light of monitoring vegetation potentially serving as nesting habitat for 3 species of management concern. We also provided directions on future monitoring to ensure that managed parcels provide suitable vegetation structure for at least some, and possibly all, of the species given their divergent habitat requirements.